Luxembourg : Financial Sector Assessment Program: Technical Note-Fund Management: Regulation, Supervision, and Systemic Risk Monitoring. (IMF Staff Country Reports; Country Report ;, 2017)
This Technical Note discusses the findings and recommendations made in the 2017 Financial Sector Assessment Program for Luxembourg in areas of regulation, supervision, and systemic risk monitoring of fund management. Certain structural elements of the Luxembourg fund management industry, particularly the extensive use of delegation and concentration of fund directorships, merit increased supervisory analysis and attention beyond the current activities. The Luxembourg framework for liquidity management tools compares favorably with its peers at both the EU and international level. Information on leverage of funds is of potential relevance from a systemic risk perspective. The Luxembourg authorities have also been actively monitoring and contributing to discussions on the EU money market funds regulation.